High-expansion-rate high-strength sealant and preparation method thereof

By using a high expansion rate and high strength sealant composed of specific resins, rubbers and other components in automobile manufacturing, the problems of lax sealing, spot welding corrosion and insufficient bonding strength are solved, and excellent sealing effect and flame retardant performance are achieved, meeting the high standards of automobile manufacturing.

CN119859488APending Publication Date: 2025-04-22HUBEI HUITIAN NEW MATERIALS STOCK CO LTD +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411948497.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In automobile manufacturing, the sealant sealant is not tightly sealed, spot welding corrosion, and insufficient bonding strength, resulting in poor sealing, serious corrosion and loose parts, affecting driving safety.

Method used

A high expansion rate and high strength sealant is used, which consists of epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler. Through specific component ratios and process processing, the expansion rate and bonding strength are improved, and the sealing performance and flame retardant are enhanced.

Benefits of technology

It achieves a high expansion rate and high strength sealing effect, ensures the improvement of sealing and bonding strength, solves the problem of spot welding corrosion, and has flame retardant performance, meeting the high standards of automobile manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a high-expansion-rate and high-strength sealant and a preparation method thereof.The high-expansion-rate and high-strength sealant is prepared by mixing epoxy resin, acrylic resin, synthetic rubber, a diluent, a tackifier, a curing agent, a foaming agent, a flame retardant and filler; wherein the synthetic rubber is composed of powdered nitrile rubber and a nitrile rubber polymer, and the powdered nitrile rubber is selected from micro-crosslinked nitrile rubber with medium acrylonitrile content and acrylonitrile mass content of 26%-29%; wherein the nitrile rubber polymer is selected from 70% of nitrile rubber and 30% of polyvinyl chloride, the nitrile rubber polymer is a rubber-plastic alloy material generated by chemical grafting reaction through an IPN network interpenetrating technology, and the acrylonitrile content of the nitrile rubber polymer is 30%-36%. According to the sealant with the high expansion rate and the high strength, the expansion rate can be increased, meanwhile, the bonding strength and the sealing performance are improved, the flame retardance is improved, and the technical requirements for the high expansion rate and the high strength are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealants, and in particular to a high-expansion rate and high-strength sealant and a preparation method thereof. Background Art

[0002] In the context of the booming automobile industry, the lightweighting of automobiles has become an irreversible trend. In order to comply with this trend, the steel plates are continuously thinned during the body manufacturing process. This is an effective measure to reduce the weight of the whole vehicle and improve fuel economy. However, it has also caused a series of thorny problems. Among them, the decline in the strength of the outer sheet metal is the most prominent. When the body sheet metal and the reinforcement are welded, many disadvantages arise.

[0003] Common conditions include: the sealing links are often full of loopholes and cannot achieve the ideal sealing effect, which allows external impurities such as water vapor and dust to easily invade, which not only affects the service life of the body parts, but may also interfere with the normal operation of the electronic components in the car; spot welding corrosion is common. Due to poor sealing of the welding points and long-term exposure to complex environments such as moisture, the corrosion process is accelerated and the stability of the body structure is seriously weakened; and insufficient bonding strength has become another "hard flaw", which cannot ensure that the various parts of the body fit closely. Under conditions such as vibration and bumps during vehicle driving, it is very easy for parts to loosen and move, posing a huge hidden danger to driving safety.

[0004] Faced with these difficulties, this field has also tried to use structural adhesives as a substitute. The introduction of structural adhesives has indeed alleviated the dilemma of insufficient bonding strength to a certain extent. With its strong bonding force, the connection between body parts is more secure. At the same time, the spot welding corrosion problem has been effectively curbed, and the welding points are better protected from corrosion. But new problems have followed one after another. In special positions where the distance between plates is large, structural adhesives are often difficult to completely fill the gaps due to the limitations of their own characteristics, and cracking occurs, and the sealing cannot be guaranteed. More importantly, the use of structural adhesives has caused production costs to rise sharply. For automobile production plants, this is undoubtedly contrary to the business goal of reducing costs and increasing efficiency, greatly compressing profit margins and limiting their large-scale promotion and application.

[0005] In the prior art, taking the high-strength, low-hardness shock-absorbing glue and its preparation method disclosed in CN201510571821.5 as an example, the design concept of the shock-absorbing glue focuses on increasing the proportion of rubber to ensure that the shock-absorbing glue has a certain shear strength, so that it can reach more than 0.7MPa, meeting the basic needs of some shock-absorbing scenarios. At the same time, in order to optimize the elasticity of the product, liquid rubber is added, and the hardness of the shock-absorbing glue is successfully reduced to 12A, so that the product shows good elastic recovery ability when buffering vibration. However, its shear strength is less than 1MPa, and it is difficult to ensure a stable connection between parts when facing the high strength requirements required for the connection of body parts. More importantly, it does not have expansion characteristics, cannot adaptively fill various gaps, and the sealing effect is greatly reduced. Naturally, it cannot play a significant reinforcing role in the body structure, and it is difficult to meet the stringent requirements for the comprehensive performance of sealants in the context of current automobile lightweighting.

[0006] Based on this, the present invention proposes a new high expansion rate and high strength sealant and a preparation method thereof. Summary of the invention

[0007] In order to solve the above problems, the present invention proposes a high-expansion rate and high-strength sealant and a preparation method thereof, which overcomes a series of difficult problems such as poor sealing of the sealant, spot welding corrosion, and insufficient bonding strength, so as to meet the requirements for the comprehensive performance of the sealant on the body of lightweight and thinned sheet metal and the welding parts with unstable plate spacing.

[0008] The technical solution of the present invention to solve the above technical problems is as follows: In a first aspect, the present invention provides a high expansion rate and high strength sealant, which is prepared by mixing the following components, each component including: epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; The synthetic rubber is composed of powdered nitrile rubber and nitrile rubber polymer, wherein the powdered nitrile rubber is selected from slightly cross-linked nitrile rubber with a medium acrylonitrile content of 26%-29% by mass; the nitrile rubber polymer is selected from a rubber-plastic alloy material generated by chemical grafting reaction of 70% nitrile rubber and 30% polyvinyl chloride using IPN network interpenetration technology, and the acrylonitrile content of the nitrile rubber polymer is 30%-36%.

[0009] Based on the above technical solution, the present invention can also be improved as follows.

[0010] Furthermore, the high expansion rate and high strength sealant component comprises the following raw materials in percentage by weight: Epoxy resin 6%-10%; Acrylic resin 8%-14%; Synthetic rubber 10%-15%; Diluent 30%-45%; Thickener 1%-4%; Curing agent 1%-2%; Foaming agent 1.5%-2.5%; Flame retardant 2%-8%; Filling 15%-35%.

[0011] Furthermore, the epoxy resin is selected from at least one of alkyl or alkoxy glycol mono / diglycidyl ether, bisphenol A diglycidyl ether and bisphenol F diglycidyl ether.

[0012] Furthermore, the acrylic resin is selected from high Tg and high hydroxyl value acrylic ester paste resins having a glass transition temperature of above 90° C. and a hydroxyl value of above 10 mgKOH / g.

[0013] Furthermore, the diluent is at least one of diisononyl phthalate and dipropylheptyl phthalate.

[0014] Furthermore, the tackifier is selected from at least one of rosin resin, phenolic resin, terpene resin and petroleum resin.

[0015] Furthermore, the curing agent is a mixture of dicyandiamide, 4,4'-methylenebis(phenyldimethylurea), and di-(tert-butylperoxyisopropyl)benzene.

[0016] Further, the foaming agent is an azo compound; The flame retardant is microencapsulated red phosphorus.

[0017] Furthermore, the filler is selected from at least one of calcium carbonate, mica powder, quartz powder, diatomaceous earth, kaolin, silicon powder, silicon dioxide, calcium oxide and carbon black.

[0018] In a second aspect, the present invention further provides a method for preparing the high expansion rate and high strength sealant as described in the first aspect, comprising the following steps: S1: Weigh various raw materials in a specific preset mass ratio, including epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; S2: placing the weighed synthetic rubber and diluent together in an environment with a temperature between 60-70°C, and continuously stirring using a stirring device until the synthetic rubber is completely dissolved in the diluent to obtain a uniform liquid mixture; S3: adding the liquid mixture obtained in step S2 and the epoxy resin, acrylic resin, tackifier, curing agent, foaming agent, flame retardant and filler weighed in step S1 to a dynamic mixer respectively, setting the temperature of the dynamic mixer to a range of 30-40° C., starting stirring, and fully stirring the components until all the raw materials are evenly dispersed to obtain an intermediate mixture; S4: placing the intermediate mixture obtained in step S3 in a vacuum environment for stirring and degassing treatment. Under the action of vacuum negative pressure, the bubbles in the mixture are removed, and a high expansion rate and high strength sealant is obtained.

[0019] Compared with the prior art, the technical solution of this application has the following beneficial technical effects: The high-expansion rate and high-strength sealant and preparation method thereof improve the expansion rate while improving the bonding strength and sealing performance and increasing the flame retardancy by optimizing specific types and proportions of components such as resin, rubber, diluent and tackifier, thereby meeting the technical requirements of high expansion rate and high strength. The sealant is used for steel plate welding parts such as automobile floors, wheel covers, side panels, and pillars, and plays the roles of bonding and sealing, waterproofing, flame retardancy, and preventing spot welding corrosion.

[0020] Specifically, the present invention focuses on the screening and optimization of raw materials, and strives to achieve an all-round breakthrough in performance by optimizing specific types of key components such as resins, rubbers, diluents and tackifiers and mixing them in precise proportions. On the one hand, the expansion rate of the sealant is improved so that it can fully extend and expand when filling the gap, and perfectly fit various complex gap structures, thereby achieving excellent sealing effects and completely eliminating the invasion of external impurities. The expansion rate of the sealant product of the present invention is increased from 0% to 322% on the basis of previous products; on the other hand, the bonding strength is greatly improved to ensure that the body parts can be closely connected under any harsh working conditions, improve stability, and escort driving safety. The shear strength is increased from 0.70MPa to 1.38MP. At the same time, the sealing performance is also strengthened, the body protection barrier is further strengthened, and the flame retardancy is innovatively increased to cope with emergencies such as high temperature and open flames that may be encountered during the operation of the car, and the high standards of automobile manufacturing are fully met.

[0021] In summary, the high expansion rate and high strength sealant provided by the present invention can not only supplement the bonding strength and tightly seal the vehicle body, but also completely solve the spot welding corrosion problem, the spot welded steel plate is corrosion-free, and the flame retardancy test shows that the fire is self-extinguishing, and it can also meet the advanced process requirements of the sealant flame retardancy and adapt to automated construction, injecting new vitality into the automobile manufacturing industry. DETAILED DESCRIPTION

[0022] The specific implementation of the present invention is described in detail below. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the protection scope of the present invention.

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0025] In the present invention, the sources of raw materials are described as follows: Epoxy resin: BE-188EL purchased from Changchun Chemical, YDF-170 was purchased from Guodu Chemical.

[0026] Acrylic resin: Acrylic resin LP3130 was purchased from Mitsubishi Chemical, Acrylic resin UC506 was purchased from KANEKA.

[0027] PVC resin: PSM-31 was purchased from Shenyang Chemical.

[0028] Synthetic rubber: Nitrile rubber NBR purchased from Saikede Rubber & Plastic Co., Ltd. Powdered nitrile rubber HLN was purchased from Anqing Hualan Technology.

[0029] Diluent: Diisononyl phthalate DINP purchased from Liancheng Chemical, Dipropylheptyl phthalate (DPHP) was purchased from Shanghai Kunrui Chemical.

[0030] Tackifier: Terpene resin purchased from Shaxian Licheng Chemical, Rosin resin was purchased from Shaxian Licheng Chemical. Phenolic resin was purchased from Qingdao Huiming.

[0031] Curing agent: dicyandiamide purchased from OMICURE, Organic urea was purchased from CVC, Di-(tert-butylperoxyisopropyl)benzene was purchased from ARKEMA, Butyl 4-bis(tert-butylperoxy)valerate was purchased from Jinan Guochen Taifu Chemical.

[0032] Foaming agent: Azodicarbonamide was purchased from Jiangsu Sopo, The microsphere foaming agent was purchased from Akzo Nobel.

[0033] Flame retardant: Microencapsulated red phosphorus was purchased from Hongtaiji Industrial.

[0034] Filler: Calcium carbonate SP200 purchased from Shanxi Lanhua, Calcium carbonate CC905 was purchased from Guangxi Kelong. Silica TS720 was purchased from CABOT, Calcium oxide was purchased from Zibo Hainuo. Carbon black M570 was purchased from CABOT. The remaining reagents are commercially available.

[0035] The high expansion rate and high strength sealant provided by the present invention is prepared by mixing the following components, wherein the components include: epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; The synthetic rubber is composed of powdered nitrile rubber and nitrile rubber polymer in a ratio of (8-15): (0-2), wherein the powdered nitrile rubber is selected from slightly cross-linked nitrile rubber with a medium acrylonitrile content of 26%-29% by mass; the nitrile rubber polymer is selected from a rubber-plastic alloy material generated by chemical grafting reaction of 70% nitrile rubber and 30% polyvinyl chloride using IPN network interpenetration technology, and the acrylonitrile content of the nitrile rubber polymer is 30%-36%.

[0036] Preferably, the high expansion rate and high strength sealant component comprises the following raw materials in percentage by weight: Epoxy resin 6%-10%; Acrylic resin 8%-14%; Synthetic rubber 10%-15%; Diluent 30%-45%; Thickener 1%-4%; Curing agent 1%-2%; Foaming agent 1.5%-2.5%; Flame retardant 2%-8%; Filling 15%-35%.

[0037] Wherein, the epoxy resin is selected from at least one of alkyl or alkoxy glycol mono / diglycidyl ether, bisphenol A diglycidyl ether and bisphenol F diglycidyl ether.

[0038] The acrylic resin is selected from a high Tg and high hydroxyl value acrylic ester paste resin having a glass transition temperature of above 90° C. and a hydroxyl value of above 10 mgKOH / g.

[0039] The diluent is at least one of diisononyl phthalate and dipropylheptyl phthalate.

[0040] The tackifier is selected from at least one of rosin resin, phenolic resin, terpene resin and petroleum resin.

[0041] The curing agent is a mixture of dicyandiamide, 4,4'-methylenebis(phenyldimethylurea) and di-(tert-butylperoxyisopropyl)benzene.

[0042] The foaming agent is an azo compound; The flame retardant is microencapsulated red phosphorus.

[0043] The filler is selected from at least one of calcium carbonate, mica powder, quartz powder, diatomaceous earth, kaolin, silicon powder, silicon dioxide, calcium oxide and carbon black.

[0044] The preparation method of the high expansion rate and high strength sealant comprises the following steps: S1: Weigh various raw materials in a specific preset mass ratio, including epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; S2: placing the weighed synthetic rubber and diluent together in an environment with a temperature between 60-70°C, and continuously stirring using a stirring device until the synthetic rubber is completely dissolved in the diluent to obtain a uniform liquid mixture; S3: adding the liquid mixture obtained in step S2 and the epoxy resin, acrylic resin, tackifier, curing agent, foaming agent, flame retardant and filler weighed in step S1 to a dynamic mixer respectively, setting the temperature of the dynamic mixer to a range of 30-40° C., starting stirring, and fully stirring the components until all the raw materials are evenly dispersed to obtain an intermediate mixture; S4: placing the intermediate mixture obtained in step S3 in a vacuum environment for stirring and degassing treatment, wherein bubbles in the mixture are removed under the action of vacuum negative pressure, thereby obtaining a high expansion rate and high strength sealant; Among them, the process parameters of vacuum stirring degassing are: vacuum pressure is not less than -0.09MPa, and degassing stirring time is 30min-40min.

[0045] The following is further introduced in conjunction with specific embodiments: Example 1 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 1 below: Table 1 Composition of sealant provided in Example 1

[0046] The preparation method of the sealant of this embodiment comprises the following steps: S1, weigh each raw material according to the component ratio provided in Table 1.

[0047] S2, stirring and mixing the synthetic rubber and the diluent at 60° C. until they are completely dissolved to obtain a liquid mixture.

[0048] S3, respectively add the liquid mixture, epoxy resin, acrylic resin, tackifier, curing agent, foaming agent, flame retardant and filler into a dynamic mixer, stir for 30 minutes at 35°C, revolution 15 Hz and rotation 30 Hz until the mixture is evenly dispersed, to obtain an intermediate mixture.

[0049] S4, degassing for 30 minutes in vacuum (vacuum pressure above -0.09MPa) under the conditions of 35℃, revolution 15Hz and rotation 10Hz.

[0050] Example 2 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 2 below: Table 2 Composition of sealant provided in Example 2

[0051] The preparation method of the sealant of this embodiment comprises the following steps: S1, weigh each raw material according to the component ratio provided in Table 2.

[0052] S2, stirring and mixing the synthetic rubber and the diluent at 70° C. until they are completely dissolved to obtain a liquid mixture.

[0053] S3, respectively add the liquid mixture, epoxy resin, acrylic resin, tackifier, curing agent, foaming agent, flame retardant and filler into a dynamic mixer, stir for 30 minutes at 40°C, revolution 15 Hz and rotation 30 Hz until the mixture is evenly dispersed, to obtain an intermediate mixture.

[0054] S4, degassing for 40 minutes in vacuum (vacuum pressure above -0.09MPa) under the conditions of 40℃, revolution 15Hz and rotation 10Hz.

[0055] Example 3 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 3 below: Table 3 Composition of sealant provided in Example 3

[0056] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0057] Example 4 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 4 below: Table 4 Composition of sealant provided in Example 4

[0058] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0059] Example 5 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 5 below: Table 5 Composition of sealant provided in Example 5

[0060] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0061] Example 6 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 6 below: Table 6 Composition of sealant provided in Example 6

[0062] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0063] Example 7 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 7 below: Table 7 Composition of sealant provided in Example 7

[0064] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0065] Example 8 This embodiment provides a sealant, which is prepared from the raw materials shown in Table 8 below: Table 8 Composition of sealant provided in Example 8

[0066] The preparation method of the sealant in this embodiment is basically the same as that in Embodiment 1, and will not be described in detail here.

[0067] Comparative Example 1 This comparative example provides a sealant, which is prepared from the raw materials shown in Table 9 below: Table 9 Composition of sealant provided in Comparative Example 1

[0068] The preparation method of the sealant in this comparative example is basically the same as that in Example 1, and will not be described in detail here.

[0069] Comparative Example 2 This comparative example provides a sealant, which is prepared from the raw materials shown in Table 10 below: Table 10 Composition of sealant provided in Comparative Example 2

[0070] The preparation method of the sealant in this comparative example is basically the same as that in Example 1, and will not be described in detail here.

[0071] Comparative Example 3 This comparative example provides a sealant, which is prepared from the raw materials shown in Table 11 below: Table 11 Composition of sealant provided in Comparative Example 3

[0072] The preparation method of the sealant in this comparative example is basically the same as that in Example 1, and will not be described in detail here.

[0073] Comparative Example 4 This comparative example provides a sealant, which is prepared from the raw materials shown in Table 12 below: Table 12 Composition of sealant provided in Comparative Example 4

[0074] The preparation method of the sealant in this comparative example is basically the same as that in Example 1, and will not be described in detail here.

[0075] Comparative Example 5 This comparative example provides a sealant, which is prepared from the raw materials shown in Table 13 below: Table 13 Composition of sealant provided in Comparative Example 5

[0076] The preparation method of the sealant in this comparative example is basically the same as that in Example 1, and will not be described in detail here.

[0077] The sealants obtained in the above examples and comparative examples were tested for performance, and the testing method is as follows: 1. Shear strength: All the test pieces used were cold-rolled steel test pieces (100mm*25mm*1.6mm). The test pieces were cleaned with acetone (or butanone), and after drying, anti-rust oil (QUAKER 6130N) was evenly applied on the surface, with an oil coating amount of about 2.5g / m2.

[0078] According to GB / T 7124 standard, the sealant was adhered between the two test pieces, with an overlap area of ​​25mm*25mm and a thickness of 3.0mm. The fixed test pieces were cured at 170℃×20min, taken out, placed at room temperature for 1h, and the clamps were removed.

[0079] The shear strength test is carried out at 23±1℃ and the unit is expressed in MPa.

[0080] 2. Flame retardancy: (1) Apply the rubber material in a shape of 100 mm × 50 mm × 5.0 mm on an oiled steel plate with dimensions of 150 mm × 75 mm × (0.7 ± 0.1) mm; (2) Bake the prepared test piece at 170°C for 20 minutes, take it out and place it in a standard environment for 24 hours before testing; (3) With the specimen surface facing downward, slightly touch the top of the flame of a gas (Bunsen) burner (about 1570 kJ / m³) to the center of the specimen, so that the top of the flame just touches the surface of the rubber sample, and maintain this state for 10 seconds; (4) Then move away from the flame and place the test piece in a vertical position. Observe and record whether the test piece can extinguish itself within 2 seconds. If it can extinguish itself, it is qualified. Otherwise, it is considered unqualified: (5) Results: Three groups of samples were evaluated in parallel, and the worst experimental result was recorded as the final conclusion.

[0081] 3. Spot welding corrosion: Apply 150 mm × 25 mm × 0.3 mm of sealant in the middle of a test plate; evenly spot weld 4 points on the glue-coated area. Carry out pretreatment and electrophoresis according to the actual production process, and then dry. Carry out neutral salt spray test for 500 h according to GB / T 10125. After the test, select a suitable drill bit, use a drill press to drill holes steadily on the welding points, and remove the test plate to check the corrosion of the area around the spot welding. Requirements: No loss of adhesion or corrosion of the base material at the joint is allowed.

[0082] 4. Expansion rate First, measure the mass m1 of a (50×50) mm aluminum plate or polytetrafluoroethylene plate in air and the mass m2 in water. Then, place 2 g of the sample on the aluminum plate or polytetrafluoroethylene plate to form a semicircle with a diameter of about 10 mm. Use a balance to weigh its mass m3 in air and m4 in water.

[0083] Then place the sample at normal baking temperature and time for baking. After cooling, measure its mass m5 in air and mass m6 in water, and calculate the volume expansion rate according to the following formula:

[0084] Where: m1——the mass of the aluminum plate (or polytetrafluoroethylene plate) in the air (g); m2——the mass of the aluminum plate (or polytetrafluoroethylene plate) in pure water (g); m3——the mass of the aluminum plate (or polytetrafluoroethylene plate) and the sample in air (g); m4——the mass of the aluminum plate (or polytetrafluoroethylene plate) and the sample in pure water (g); m5——The mass of the baked aluminum plate (or polytetrafluoroethylene plate) and the sample in the air (g); m6——The mass of the baked aluminum plate (or polytetrafluoroethylene plate) and the sample in pure water (g).

[0085] Performance Test Results Table 13 Performance test results statistics

[0086] Combined with the performance test result table, it can be seen that compared with comparative examples 1 to 5, the high expansion rate and high strength sealants of Examples 1 to 8 improve the expansion rate while improving the bonding strength and sealing performance, increasing the flame retardancy, and meeting the technical requirements of high expansion rate and high strength by optimizing specific types and proportions of components such as resin, rubber, diluent and tackifier.

[0087] Specifically, based on previous products, the expansion rate of the sealant product of the present invention is increased from 0% to 322%, and the shear strength is increased from 0.70MPa to 1.38MPa. The spot-welded steel plate is corrosion-free, and the flame retardancy test shows that the fire is self-extinguishing, thereby achieving the goal of supplementing the adhesive strength of the sealant, sealing the vehicle body, and solving the spot welding corrosion problem, while meeting the process requirements of the sealant flame retardancy and automated construction.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high expansion rate and high strength sealant, characterized in that: The invention is prepared by mixing the following components, wherein the components include: epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; The synthetic rubber is composed of powdered nitrile rubber and nitrile rubber polymer, wherein the powdered nitrile rubber is selected from slightly cross-linked nitrile rubber with a medium acrylonitrile content of 26%-29% by mass; the nitrile rubber polymer is selected from a rubber-plastic alloy material generated by chemical grafting reaction of 70% nitrile rubber and 30% polyvinyl chloride using IPN network interpenetration technology, and the acrylonitrile content of the nitrile rubber polymer is 30%-36%.

2. The high expansion rate and high strength sealant according to claim 1, characterized in that: The high expansion rate and high strength sealant component comprises the following raw materials in percentage by weight: Epoxy resin 6%-10%; Acrylic resin 8%-14%; Synthetic rubber 10%-15%; Diluent 30%-45%; Thickener 1%-4%; Curing agent 1%-2%; Foaming agent 1.5%-2.5%; Flame retardant 2%-8%; Filling 15%-35%.

3. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The epoxy resin is selected from at least one of alkyl or alkoxy glycol mono / diglycidyl ether, bisphenol A diglycidyl ether and bisphenol F diglycidyl ether.

4. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The acrylic resin is selected from a high Tg and high hydroxyl value acrylic ester paste resin having a glass transition temperature of above 90° C. and a hydroxyl value of above 10 mgKOH / g.

5. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The diluent is at least one of diisononyl phthalate and dipropylheptyl phthalate.

6. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The tackifier is selected from at least one of rosin resin, phenolic resin, terpene resin and petroleum resin.

7. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The curing agent is a mixture of dicyandiamide, 4,4'-methylenebis(phenyldimethylurea) and di-(tert-butylperoxyisopropyl)benzene.

8. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The blowing agent is an azo compound; The flame retardant is microencapsulated red phosphorus.

9. The high expansion rate and high strength sealant according to claim 1 or 2, characterized in that: The filler is selected from at least one of calcium carbonate, mica powder, quartz powder, diatomaceous earth, kaolin, silicon powder, silicon dioxide, calcium oxide and carbon black.

10. A method for preparing a high expansion ratio and high strength sealant according to any one of claims 1 to 9, characterized in that: The steps include: S1: Weigh various raw materials in a specific preset mass ratio, including epoxy resin, acrylic resin, synthetic rubber, diluent, tackifier, curing agent, foaming agent, flame retardant and filler; S2: placing the weighed synthetic rubber and diluent together in an environment with a temperature between 60-70°C, and continuously stirring using a stirring device until the synthetic rubber is completely dissolved in the diluent to obtain a uniform liquid mixture; S3: adding the liquid mixture obtained in step S2 and the epoxy resin, acrylic resin, tackifier, curing agent, foaming agent, flame retardant and filler weighed in step S1 to a dynamic mixer respectively, setting the temperature of the dynamic mixer to a range of 30-40° C., starting stirring, and fully stirring the components until all the raw materials are evenly dispersed to obtain an intermediate mixture; S4: placing the intermediate mixture obtained in step S3 in a vacuum environment for stirring and degassing treatment. Under the action of vacuum negative pressure, the bubbles in the mixture are removed, and a high expansion rate and high strength sealant is obtained.

Citation Information

Patent Citations

  • A kind of high-strength, low-hardness shock-absorbing glue and preparation method thereof

    CN105175816B